2015
DOI: 10.1016/j.alit.2014.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Periostin contributes to epidermal hyperplasia in psoriasis common to atopic dermatitis

Abstract: Background Epidermal hyperplasia is a histological hallmark observed in both atopic dermatitis (AD) and psoriasis, although the clinical features and the underlying immunological disorders of these diseases are different. We previously showed that periostin, a matricellular protein, plays a critical role in epidermal hyperplasia in AD, using a mouse model and a 3-dimensional organotypic coculture system. In this study, we explore the hypothesis that periostin is involved in epidermal hyperplasia in psoriasis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 29 publications
4
38
0
Order By: Relevance
“…Additionally, Shin et al1 found that human epidermal keratinocytes (SV-HEKs), which were fully differentiated displayed significantly higher PAR-2 expression than undifferentiated keratinocytes, which is in accordance with similar previous findings. This corresponds well with the fact that both aforementioned skin conditions; atopic dermatitis and psoriasis involves substantial epidermal hyperplasia5, in addition to PAR-2 associated sensory symptoms, most prominently itch, cutaneous inflammation and mild pain.…”
supporting
confidence: 84%
“…Additionally, Shin et al1 found that human epidermal keratinocytes (SV-HEKs), which were fully differentiated displayed significantly higher PAR-2 expression than undifferentiated keratinocytes, which is in accordance with similar previous findings. This corresponds well with the fact that both aforementioned skin conditions; atopic dermatitis and psoriasis involves substantial epidermal hyperplasia5, in addition to PAR-2 associated sensory symptoms, most prominently itch, cutaneous inflammation and mild pain.…”
supporting
confidence: 84%
“…The remaining excised skin was cut into about 2 mm thick transverse slices and fixed in 10% formalin. Sections of 3-5 lm thickness were stained with haematoxylin and eosin (H&E), naphthol AS-D chloroacetate esterase and toluidine blue for detecting epidermal thickness [15], inflammatory cells such as neutrophil and mast cells, respectively. A histomorphological evaluation of all the skin sections was carried out in a blinded fashion [14].…”
Section: Histopathological Studiesmentioning
confidence: 99%
“…Quantitative RT‐PCR was performed as previously described . Briefly, total RNA was prepared using an RNAiso plus reagent (Takara Bio, Otsu, Japan), and reverse‐transcribed with the ReverTra Ace (TOYOBO, Osaka, Japan).…”
Section: Methodsmentioning
confidence: 99%